Examining the key factors behind foreign language anxiety (FLA) in online teaching of English for Specific Purposes (ESP) - Lađarević Maja Novak (ExELL (Explorations in English Language and Linguistics))
Though foreign language anxiety (FLA) has long been recognized as an important affective factor in second language learning, its impact is worth studying in new educational contexts of emergency remote teaching in response to the COVID-19 outbreak. The present study examines the key factors behind FLA in online teaching of English for Specific Purposes (ESP). The research was conducted among a sample of 171 first-year undergraduate university students of Economics & Business economics and Informatics at the Juraj Dobrila University of Pula, Croatia, during the winter semester of 2020/2021. The research instrument used was a 33-item questionnaire adapted from the FLCAS scale (Horwitz et al., 1986) to reflect the online ESP classroom environment. The main results indicate that various background factors, such as gender, self-assessed levels of proficiency, length of learning English and frequency of English language use, significantly influence the reported levels of language anxiety. Furthermore, the study establishes the underlying structure of FLA, with five factors positively correlated with overall language anxiety at the. 01 level of statistical significance: speech anxiety, evaluation and comprehension anxiety, online ESP classroom environment, anxiety of talking to native speakers, and lack of motivation for online class attendance. Finally, multiple regression analysis shows that the five aspects of FLA, alongside the variables of gender and self-assessed pronunciation proficiency, represent statistically significant predictors of the total level of FLA among online ESP learners. The other independent variables are confirmed to be unreliable in predicting the overall level of language anxiety in an online ESP classroom.